2004
DOI: 10.1097/00043426-200404000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase Antibody and Asparaginase Activity in Children With Higher-Risk Acute Lymphoblastic Leukemia

Abstract: We investigated the anti-asparaginase antibody (Ab) and asparaginase enzymatic activity in the sera of 1,001 patients (CCG-1961) with high-risk acute lymphoblastic leukemia (HR-ALL). Patients received nine doses of native Escherichia coli asparaginase during induction. Half of rapid early responders (RER) were randomly assigned to standard intensity arms and continued to receive native asparaginase. The other RER patients and all slow early responders received 6 or 10 doses of PEG-asparaginase. Serum samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
230
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(254 citation statements)
references
References 27 publications
9
230
1
14
Order By: Relevance
“…She had an initial significant decrease in size of the abdominal masses, but re-evaluation after cycle #3 showed regrowth of the abdominal adenopathy. She then received four-drug acute lymphoblastic leukemia (ALL)-like induction chemotherapy with vincristine, daunorubicin, PEG asparaginase and prednisone with intrathecal methotrexate [10]. She had a dramatic response to this therapy with complete disappearance of abdominal disease.…”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…She had an initial significant decrease in size of the abdominal masses, but re-evaluation after cycle #3 showed regrowth of the abdominal adenopathy. She then received four-drug acute lymphoblastic leukemia (ALL)-like induction chemotherapy with vincristine, daunorubicin, PEG asparaginase and prednisone with intrathecal methotrexate [10]. She had a dramatic response to this therapy with complete disappearance of abdominal disease.…”
Section: Case Reportsmentioning
confidence: 99%
“…Her pre-transplant EBV status was unknown. ALL induction therapy, as given in case #1 [10], was complicated by pancreatitis, and posterior reversible encephalopathy syndrome. Following completion of induction chemotherapy she had complete resolution of abdominal nodal disease, but the abnormal T-cell clone persisted at a low-level in the marrow and CSF in conjunction with interstitial lung disease.…”
Section: Case Reportsmentioning
confidence: 99%
“…Children and adolescents with ALL who receive an inadequate course of planned asparaginase therapy due to either intolerable side effects or silent inactivation have been shown to have inferior outcomes compared with those who receive the majority of intended doses of asparaginase, highlighting the importance of maximizing the delivery of planned asparaginase therapy. [1][2][3] L-asparaginase preparations are bacterial enzymes derived from either Escherichia coli (E. coli) or Erwinia chrysanthemi (Erwinia). E. coli-derived preparations include native E. coli-asparaginase, no longer available in the United States, and pegylated formulations (pegaspargase), in which the E. coli-derived enzyme is modified by the covalent attachment of polyethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism appears to be the production of anti-asparaginase antibodies in the host cells, which neutralize L-asparaginases impeding their enzymatic activity (Chakrabarti and Schuster). Some studies have shown that the incidence of hypersensitivity to asparaginase is similar between age groups; others suggested that infants and younger patients develop antibody and hypersensitivity reactions less frequently than teenagers and adult patients [79]. Antibodies produced in response to asparaginase do not always lead to clinical hypersensitivity instead cause rapid inactivation of the asparaginase, resulting in Sub optimal asparagines depletion.…”
Section: Toxicity Of Amidases: Hypersensitivitymentioning
confidence: 99%